A cinchona alkaloid catalyzed enantioselective sulfa-Michael/aldol cascade reaction of isoindigos: construction of chiral bispirooxindole tetrahydrothiophenes with vicinal quaternary spirocenters1. Issue 22 (14th June 2015) - Gui, Yong-Yuan; Yang, Jian; Qi, Liang-Wen; Wang, Xiao; Tian, Fang; Li, Xiao-Nian; Peng, Lin; Wang, Li-Xin
<x xml:space="preserve">Abstract</x> Enantioselective sulfa-Michael/aldol reaction of isoindigos has been successfully developed to afford bispirooxindole tetrahydrothiophenes with vicinal quaternary spirocenters.